2016
DOI: 10.1063/1.4938711
|View full text |Cite
|
Sign up to set email alerts
|

Mean transverse momenta correlations in hadron-hadron collisions in MC toy model with repulsing strings

Abstract: Abstract. In the present work, Monte-Carlo toy model with repulsing quark-gluon strings in hadron-hadron collisions is described. String repulsion creates transverse boosts for the string decay products, giving modifications of observables. As an example, long-range correlations between mean transverse momenta of particles in two observation windows are studied in MC toy simulation of the heavy-ion collisions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This should give not only enhanced transverse momenta, in particular for high mass particles, but would also give rise to angular correlations. Such correlations were early considered by Abramovsky et al [29], and a Monte Carlo "toy model" studying this effect in PbPb collisions was presented in [30].…”
Section: Introduction -mentioning
confidence: 99%
“…This should give not only enhanced transverse momenta, in particular for high mass particles, but would also give rise to angular correlations. Such correlations were early considered by Abramovsky et al [29], and a Monte Carlo "toy model" studying this effect in PbPb collisions was presented in [30].…”
Section: Introduction -mentioning
confidence: 99%
“…[32], includes the decrease in the effective string tension and, therefore, should lead to the string repulsion (see also Ref. [33]).…”
Section: Fusion and The Kinetic Energy Of Stringsmentioning
confidence: 99%
“…It creates distinct directions of motion in the transverse plane for particles originating from the rearranged colour field. This approach originates from the pioneering paper [32] and has already been tested in more recent models [33,34]. The interplay of these two mechanisms, driven by string fusion, allows one to obtain specific joint correlations in pseudorapidity and azimuthal angle, η and φ, respectively, of the same origin in collision systems of different types.…”
Section: Introductionmentioning
confidence: 99%
“…In the pp community, much attention have been given to models of final state interactions including colour reconnections, rope hadronisation and junction formation [67][68][69]. These models have, in pp been shown to reproduce: the enhancement of strange hadrons to non-strange hadrons in dense environments [70]; flowlike effects in hadron ratios as function of p ⊥ ; and preliminary studies have shown that interactions between strings can produce a ridge [71].…”
Section: Outlook: Modelling Collective Effectsmentioning
confidence: 99%